2015
DOI: 10.1007/s12217-015-9443-z
|View full text |Cite
|
Sign up to set email alerts
|

Responds of Bone Cells to Microgravity: Ground-Based Research

Abstract: Severe loss of bone occurs due to long-duration spaceflight. Mechanical loading stimulates bone formation, while bone degradation happens under mechanical unloading. Bone remodeling is a dynamic process in which bone formation and bone resorption are tightly coupled. Increased bone resorption and decreased bone formation caused by reduced mechanical loading, generally result in disrupted bone remodeling. Bone remodeling is orchestrated by multiple bone cells including osteoblast, osteocyte, osteoclast and mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…As we all know, bone remodeling depends on the dynamic balance in normal bones. It has been shown that microgravity environment breaks the balance between them, which may count for the bone loss [33]. At the same time, the effects of microgravity on osteoblast alterations have been widely reported, including reduced proliferation, activity and osteoblastic function of osteoblast, as well as inhibition the response to bone related factors [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, bone remodeling depends on the dynamic balance in normal bones. It has been shown that microgravity environment breaks the balance between them, which may count for the bone loss [33]. At the same time, the effects of microgravity on osteoblast alterations have been widely reported, including reduced proliferation, activity and osteoblastic function of osteoblast, as well as inhibition the response to bone related factors [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, osteoblast differentiation and mineralization were inhibited in HyMF of 500 nT through restraining the activity of ALP, the deposition of calcium and the formation of mineralized nodule. During long-term space exploration, osteoporosis tends to occur especially in load-bearing bone for astronauts due to lacked gravity stress [ 42 , 43 ]. Data from Mir and ISS space stations shows that mechanical stimulation in the form of exercise is still not enough to prevent bone loss in long-duration spaceflight [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then placed in a random positioning machine (Center for Space Science and Applied Research, Chinese Academy of Sciences), as described. 22 The rotation direction and speed (varied from 0 to 10 rpm) were random. During cell culture, the random positioning machine was placed in an incubator at 37 掳C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…C2C12 cells (1 脳 10 6 ) were seeded on carrier slides placed in six-well plates overnight. The cells were then placed in a random positioning machine (Center for Space Science and Applied Research, Chinese Academy of Sciences), as described . The rotation direction and speed (varied from 0 to 10 rpm) were random.…”
Section: Methodsmentioning
confidence: 99%